Avaliação da política pública de fiscalização integrada e Fortaleza Online, a partir da criação da Agência de Fiscalização de Fortaleza (AGEFIS) - Verçosa, Mariana Lima Castelo Branco (2022)
This study has as main objective to evaluate the public policies of integrated inspection and online fortress, from the creation of the Inspection Agency of Fortaleza – Agefis, December 2014, seeking to analyze the efficiency of these two innovative public policies, which underwent several changes and redefinitions throughout its history, corroborating with the rupture of the patrimonial, bureaucratic State, for the managerial State deepened by Bresser Pereira (2001). These public policies will be evaluated from the perspective of the Agency's employees, especially inspectors with field experience, since municipal inspection plays an important role in the planning of the city, balance of collective relations and fulfillment of rights and duties, guided by the principle of legality, which outlines the limits of its action. The specific objectives are to understand the concepts of integrated inspection and online fortitude; to identify how the integrated inspection and the online fortress are related and to perceive both policies especially through the eyes and experiences of the inspection agents of urban activity and health surveillance in the city of Fortaleza. The work proposes as a methodology a qualitative approach, supported by the perspective of in-depth evaluation, proposed by Rodrigues (2011), which focuses on four analytical axes: content analysis, context analysis, institutional trajectory and temporal and territorial spectrum. Data collection included a bibliographic research, documental data search analysis of institutional documents and structured interviews carried out with three categories of subjects: 10 field inspectors, 06 inspectors with a commissioned position and 04 commissioned servers from Agefis. The method used to assess the data was the analysis of the content of the speeches, starting with a pre-analysis, followed by the definition of categories of interest and ending with the interpretation of results. The result of the field research showed that both policies bring more positive aspects than the previous formats of inspection and licensing, however, it deserves attention by public managers about the need for constant monitoring and evaluation of these policies. It was identified that the two policies would form a perfect marriage if they went together, however an inoperative inspection was noticed regarding the inspections of self-declared licensing, and regarding the online fortress, a feeling of numerous licenses approved without having qualitative data whether they should or could be licensed.